Needs and preferences of women users of oral contraceptives in selected countries in Central and Eastern Europe - Tomas Fait; Dmitry Buryak; Monica-Mihaela Cirstoiu; Eva Luczai; Rafal Janczura (Drugs in Context, 2018)
Background: The availability of various oral contraceptive (OC) pill formulations with different hormone compositions suggests that there is potential to align a particular product with an individual user’s needs and preferences. To explore this concept further, a survey was conducted of current users of OCs to define and confirm areas of specific needs, and to gain insight into their views and preferences for OC formulations.